2015
DOI: 10.1016/j.jhazmat.2015.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of domino effect in pipelines

Abstract: Parallel pipelines are frequently installed over long distances, due to the difficulty in creating or maintaining the required corridor. This implies that a release in one pipeline can seriously affect another one. The main risks associated with this domino effect are the erosive action of fluid-sand jets and the thermal action of jet fires. In this paper a survey has been performed on the accidents that have occurred, and the diverse possibilities and the associated domino sequences are analysed. The probabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 21 publications
0
13
0
3
Order By: Relevance
“…Although there are not many studies covering the projected flame height (H p ), it was reported that a study for the flame height is relatively important for jet flame impingement probability estimation for any plant installation in close vicinity. 28 Moreover, the knowledge of projected flame height enables the estimation of jet flame coverage on the target unit and the related radiative fraction that might be affected by the presence of an obstacle near the jet source. In this study, the projected flame height is increased and then decreases at higher release flowrate, as can be seen in Figure 8.…”
Section: Flame Projected Heightmentioning
confidence: 99%
“…Although there are not many studies covering the projected flame height (H p ), it was reported that a study for the flame height is relatively important for jet flame impingement probability estimation for any plant installation in close vicinity. 28 Moreover, the knowledge of projected flame height enables the estimation of jet flame coverage on the target unit and the related radiative fraction that might be affected by the presence of an obstacle near the jet source. In this study, the projected flame height is increased and then decreases at higher release flowrate, as can be seen in Figure 8.…”
Section: Flame Projected Heightmentioning
confidence: 99%
“…From a risk perspective, the PLOD are subject not only to the failure factors of a single pipeline, but also to the effects of adjacent pipeline failures, which has been proven by numerical simulations and experiments by scholars. Studies show that jet fire and explosion shock waves caused by pipeline failure will affect adjacent pipelines, that is to say, there is a failure correlation between pipelines [25][26][27][28]. Therefore, the potential danger of the pipelines and the routing environment can be upgraded.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a review of relevant literature indicated that studies on domino effects have focused on identifying the threats as well as individual and social risks–induced by such effects , establishing criteria to assess the possibility of domino effects , adopting active (e.g., sprinklers) or passive (e.g., safety distance, firewalls, and blast walls) strategies to prevent these effects from continuously expanding , and employing these strategies to contain the domino effects induced by liquid petroleum gas and propane storage tank bases or corroded pipelines . In short, these studies have proposed strategies to prevent domino effects originating from atmospheric or pressure storage tanks and pipelines.…”
Section: Introductionmentioning
confidence: 99%